Strategic Human Resource Management: Descriptive Analysis of Psychological Factors and Literature Review - Pantih, Suwardhi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to examine the impact of psychological factors on Strategic Human Resource Management (SHRM) practices and organizational outcomes. The research employs a comprehensive literature review approach to explore the theoretical underpinnings of employee motivation, engagement, and commitment within the context of SHRM. The analysis focuses on key psychological theories, including expectancy theory, social exchange theory, and self-determination theory, to elucidate the motivational dynamics underlying employee behavior and performance outcomes. Moreover, the study investigates the role of leadership effectiveness in influencing employee motivation, engagement, and organizational commitment. Through the integration of diverse perspectives, the research offers insights into how organizations can align HR practices with employees' psychological needs to enhance organizational effectiveness and achieve sustainable growth. The findings highlight the significance of fostering transformational leadership behaviors, creating a supportive work environment, and promoting organizational commitment to drive high performance and employee well-being. This study contributes to the advancement of HRM scholarship by providing a theoretical framework for understanding and managing human capital effectively.